Letter and Category Fluency Performance Correlates with Distinct Patterns of Cortical Thickness in Older Adults. (17th May 2018) - Vonk, Jet M J; Rizvi, Batool; Lao, Patrick J; Budge, Mariana; Manly, Jennifer J; Mayeux, Richard; Brickman, Adam M
Abstract: Verbal fluency tasks are generally thought to be mediated by frontal brain regions for letter fluency and temporal regions for category fluency. This idea, however, is primarily based on lesion studies and adapted versions of the fluency tasks in functional neuroimaging, without fundamental evidence from structural neuroimaging in healthy individuals. We investigated the cortical structural correlates of letter and category fluency, including overlapping and different regions, in 505 individuals who participated in a community-based study of healthy aging. The correlation between cortical thickness and verbal fluency in whole-brain analyses revealed distinct cortical signatures for letter fluency, primarily in frontal regions, and category fluency, in frontal and temporal-parietal regions. There was a dissociation in the left inferior frontal gyrus between letter and category fluency, with increased thickness in the posterior-dorsal versus anterior-ventral parts, respectively. These results distinguish the detailed anatomical correlates for verbal fluency within the coarse frontal-temporal distinction inferred from lesion studies and among the mixture of regions identified in functional neuroimaging. The evidence for the anatomical substrates of letter and category fluency, each recruiting slightly different language and cognitive processes, can serve both clinical applications as well as a deeper theoretical understanding of the organization of the cerebral cortex.